Gut-Derived Metabolite Indole-3-Propionic Acid Modulates Mitochondrial Function in Cardiomyocytes and Alters Cardiac Function - Gesper, Maren; Nonnast, Alena B. H.; Kumowski, Nina; Stoehr, Robert; Schuett, Katharina; Marx, Nikolaus; Kappel, Ben A. (Frontiers in Medicine, 2021)
Background: The gut microbiome has been linked to the onset of cardiometabolic diseases, in part facilitated through gut microbiota-dependent metabolites such as trimethylamine-N-oxide. However, molecular pathways associated to heart failure mediated by microbial metabolites remain largely elusive. Mitochondria play a pivotal role in cellular energy metabolism and mitochondrial dysfunction has been associated to heart failure pathogenesis. Aim of the current study was to evaluate the impact of gut-derived metabolites on mitochondrial function in cardiomyocytes via an in vitro screening approach. Methods: Based on a systematic Medline research, 25 microbial metabolites were identified and screened for their metabolic impact with a focus on mitochondrial respiration in HL-1 cardiomyocytes. Oxygen consumption rate in response to different modulators of the respiratory chain were measured by a live-cell metabolic assay platform. For one of the identified metabolites, indole-3-propionic acid, studies on specific mitochondrial complexes, cytochrome c, fatty acid oxidation, mitochondrial membrane potential and reactive oxygen species production were performed. Mitochondrial function in response to this metabolite was further tested in human hepatic and endothelial cells. Additionally, the effect of indole-3-propionic acid on cardiac function was studied in isolated perfused hearts of C57BL/6J mice. Results: Among the metabolites examined, microbial tryptophan derivative indole-3-propionic acid could be identified as a modulator of mitochondrial function in cardiomyocytes. While acute treatment induced enhancement of maximal mitochondrial respiration (+21.5 ± 7.8%, p<0.05), chronic exposure led to mitochondrial dysfunction (-18.9 ± 9.1%; p<0.001) in cardiomyocytes. The latter effect of indole-3-propionic acids could also be observed in human hepatic and endothelial cells. In isolated perfused mouse hearts, indole-3-propionic acid was dose-dependently able to improve cardiac contractility from +26.8 ± 11.6% (p<0.05) at 1µM up to +93.6 ± 14.4% (p<0.001) at 100µM. Our mechanistic studies on indole-3-propionic acids suggest potential involvement of fatty acid oxidation in HL-1 cardiomyocytes. Conclusion: Our data indicate a direct impact of microbial metabolites on cardiac physiology. Gut-derived metabolite indole-3-propionic acid was identified as mitochondrial modulator in cardiomyocytes and altered cardiac function in an ex vivo mouse model.